THE EFFECTIVENESS OF LEARNING MEDIA BASED ON YOUTUBE VIDEO TUTORIALS ON STUDENT LEARNING OUTCOMES PER WELDING PRACTICE - Ainun Athar, Muhammad; Huda, Khoirul; Eko Cahyanto, Septian; Kriswanto, Kriswanto; Bayu Kristiawan, Ruben; TriLaksono, Galih (Jurnal Pendidikan Teknik Mesin, 2025)
This study aims to analyze the effectiveness of YouTube-based video tutorial learning media in improving students' cognitive learning outcomes in Shielded Metal Arc Welding SMAW practice at SMK Negeri 4 Semarang. The background of this research is based on the limited use of contextual and engaging instructional media in vocational education, which leads to low conceptual understanding and applied skills among students. The research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 60 tenth-grade students from the Mechanical Engineering Expertise Program, selected through purposive sampling and divided into two groups: an experimental group that used YouTube-based instructional videos and a control group that applied conventional lecture methods. The research instrument comprised 20 validated multiple-choice questions. Data was analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, independent t-test, and N-Gain analysis to assess learning improvement. The results indicated a significant difference between the experimental and control groups p< 0.001, with the experimental group achieving an average post-test score of 84.50 and an N-Gain of 0.6100 high category. In contrast, the control group scored an average of 75.33 with an N-Gain of 0.4155 medium category. These findings suggest that using YouTube video tutorials as instructional media effectively enhances students' learning outcomes in welding practice while also creating a more contextual, visual, and student-centred learning process suited to the learning styles of vocational students.